Model to Decıde Resıdentıal Property Rents ın Tourısm Destınatıon: Specıal Reference to Hıkkaduwa Tourısm Cıty, Srı Lanka - Kanchana Jayahansi Dissanayake, Prathibhani Bandusena (International Journal of Advanced Science and Technology, 2020)
Housing is one of the basic needs of a human bean. Renting residential properties have become one of the emerging trends in the real estate industry. Therefore, landowners expecting a maximum profit from their own property. Further, tenants expect a fair value for their decision on renting a house. This renting and buying decisions are shaping by the various determinants based on the purpose. In fact, determinants influence on deciding rental values based on the location. Most of the tourism cities’ residential properties are renting and this becomes the main income source of the residents who live in tourism destinations. This research focuses an investigating determinant of residential property rents in tourism destination and develops a model to decide residential value based on determinants special reference to Hikkaduwa town area. To achieve said objective literature review supported to identified factors determine residential property rents. Further, basically within a tourism destination, both foreign and local people are demanding for rental residential properties. Based on the bivariate correlation, the determinants derived from the literature review had correlated with the rental values of residential property separately for foreign people and local people. Since literature, reviews & pilot survey proved that there are different determinants for deciding rental values for foreign and local tourists. The study used probabilistic systematic sample method to select 166 samples from 15 Grama Niladhari Divisions in Hikkaduwa town area. Data collection was completely based on a structured questionnaire survey. Finally, the derived model to identify property values for foreign people and local people separately. According to the results the residential properties which close to the coastal area demanding by foreigners. The most inland area occupied by local tenants. This model support to identify residential property values and determinant factors for rental value in tourist destinations. This study paves the path for decision-makers related to the residential property rents and decisions regarding the attributes influenced by residential property rents within the tourism environment. Further, the methodology can be adapted to any tourism cities to identify proper residential rental property values.